Kinematics and Dynamics Analysis of Double Rocker Prosthetic Knee Joint - Xuhui Liu; Zhijuan Ding; Qiwen Luo; Zhen Jian; Yuanfang Zhang (Jixie chuandong)
Knee joint is an important part of normal movements of human body. In order to meet the needs of lower limb amputees to restore normal motor function， a prosthetic knee joint with double rocker mechanism is designed. Firstly， a simplified model of the lower prosthesis is established， and the relevant parameters such as joint angle， angular velocity and angular acceleration are obtained through kinematic analysis of the model. The equilibrium equations between output damping force and driving torque were obtained through the dynamic static analysis method. The highly similar tracks and ankle motion knee instantaneous center curve contrast figure were obtained through Adams simulation analysis. The results indicate that this design of double rocker prosthetic knee joint has favorable stability and bionic performance， and can meet the demand of the movement of the amputee. It provides theoretical basis for the design， processing and real-time control of the whole structure of the double rocker prosthetic knee joint.